Enhancing Legal Awareness Among High School Students through Education and Counselling: A Case Study at SMA Negeri 45 Maluku Tengah, Indonesia - Fransina Latumahina; Muhaimin Haris Nurlette; Lukman Hakim Somar (Indonesian Journal of Cultural and Community Development, 2023)
This article presents a case study conducted at SMA Negeri 45 Maluku Tengah, Indonesia, focusing on the implementation of an educational and counselling program aimed at increasing legal awareness among high school students. The study utilized a participatory action research approach, with KKN (Community Service Program) undertaken by students from Universitas Pattimura. The research objectives were to develop students' understanding of the importance of education and counselling in promoting legal awareness, shape their attitudes towards law compliance, and motivate them to achieve their aspirations. Through the integration of theoretical knowledge and practical engagement, the program aimed to instill a sense of responsibility and prevent negative behaviors and exposure to harmful influences. The findings indicated that the program successfully increased legal awareness among the students, resulting in improved behavior, mental resilience, intellectual growth, and emotional well-being. This study highlights the significance of education and counselling initiatives in cultivating legal consciousness among high school students, serving as a guide for educators and relevant stakeholders. The implications of this research emphasize the need for further exploration and implementation of similar programs to foster positive attitudes towards the law and encourage personal development among youth, ultimately contributing to a just and law-abiding society. Indonesia is a country that is based on law, therefore all citizens in it are obliged to comply with existing laws, and have the right to receive legal protection in accordance with applicable laws and regulations. Awareness of the law among high school students, so that it can motivate and become an image for students to avoid negative traits and avoid promiscuity. thereby increasing the spirit in terms of mental, intellectual and emotional. And provide motivation in achieving every goal.Highlight: Importance of Education and Counselling: The integration of education and counselling programs plays a crucial role in increasing legal awareness among high school students, enabling them to understand the significance of law in their lives. Character Development: The programs aim to shape the behavior and characteristics of students, fostering a sense of responsibility, compliance with the law, and motivation to achieve their aspirations. Mental, Intellectual, and Emotional Growth: By enhancing legal awareness, students experience an overall improvement in their mental resilience, intellectual capacity, and emotional well-being, contributing to their personal development. Keyword: Legal Wareness, Education and Counselling, High School Students, Community Service, Character Development.